Supply Chain Digitalization, Green Supply Chain, Supply Chain Resilience Toward Competitiveness and MSMEs Performance - Zainurrafiqi, Zainurrafiqi; Gazali, Gazali (Universitas Brawijaya, Indonesia, 2024)
MSMEs that previously only relied on human resources are now forced to keep up with the times by utilizing IT in every process, from raw material procurement, production processes to distribution processes in order to remain competitive in facing a business world full of challenges. Information Technology, which is closely related to digitalization, can help companies gain sustainable competitiveness in the supply chain by improving certain asset relationships, facilitating information exchange, and building long-term cooperative relationships as a form of implementing Supply Chain Digitalization. The ability of MSMEs to implement green supply chain management is a unique ability to improve company performance. For example, a company can reduce production costs by involving its suppliers in several green initiatives, such as material recycling, environmentally friendly packaging, and efficient use of energy. Companies with high supply chain resilience will be strong and grow significantly in the face of crises, thereby minimizing losses. Therefore, companies with good supply chain resilience will have a competitive edge so they can grow faster and win the competition from their competitors. For this reason, this study aimed to examine the effect of supply chain digitization, green supply chain, and supply chain resilience on competitiveness. This research is Explanatory Research. Data collection uses a questionnaire. The sampling technique uses purposive sampling. The total sample was 400 MSMEs Managers in Pamekasan Regency, and used data analysis, namely Structural Equation Model (SEM) with AMOS software. The results highlighted that Supply Chain Digitalization, Green Supply Chain and Supply Chain Resilience has a direct and significant influence on MSMEs Performance. Moreover, Competitiveness partially mediates the relationship between Supply Chain Digitalization, Green Supply Chain and Supply Chain Resilience and MSMEs Performance. The findings of this study suggest that managers should be made aware that Supply Chain Digitalization, Green Supply Chain, Supply Chain Resilience can be an important driver for Competitiveness which in turn would enhance MSMEs Performance.